Biodegradation and detoxification of reactive orange 16 by Candida sake 41E. (September 2021) - Ruscasso, F.; Cavello, I.; Butler, M.; Loveira, E. Lopez; Curutchet, G.; Cavalitto, S.
Abstract: This investigation was aimed at studying reactive orange 16- (RO-16) dye biodegradation by the Antarctic yeast Candida sake 41E. Dye decolorization reached 94.3% (an initial 100 mg.l −1 ) within 48 h in a stirred-tank bioreactor at a specific decolorization rate of 0.09 mg.RO-16.g −1 .h −1 . The presence of reactive dye in the medium did not affect yeast growth. A specific growth rate (μ) of 0.09 h −1 and biomass yield (Yx/s) of 0.23 CmolX.CmolS −1 were obtained. Reversed-phase ultrahigh-performance-liquid-chromatography–mass-spectrometry analysis was performed to investigate the by-products generated during the biodegradation. Five yeast-catalyzed reaction products of RO-16 were identified and a biodegradation pathway for this azo dye thus proposed. In addition, the toxicity of the dye and by-products generated was assessed with Lactuca sativa L. seeds, confirming the phytotoxicity of RO-16 and its decrease after 48 h of treatment with C. sake 41E. Graphical abstract: Unlabelled Image Highlights: Candida sake 41E was used for the degradation of an azo dye (RO-16). RO-16 degradation was studied using a stirred-tank bioreactor. Toxicity, kinetic and stoichiometric analysis of RO-16 degradation were evaluated. A degradation pathway of RO-16 by C. sake 41E was proposed. Simulated wastewater of RO-16 resulted to be less toxic after 48 h of treatment.